1986
DOI: 10.1007/bf01955558
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of the inhibitor of thromboxane A2-synthetase OKY-046

Abstract: Acute renal failure (ARF) was associated with increased urinary thromboxane (TXA2) excretion and lessened excretion of sodium (UNaV) and fractional excretion of sodium (FENa%). The inhibitor of thromboxane A2-synthetase OKY-046 enhanced sodium excretion and fractional excretion of sodium in normal and saline loaded animals whereas it partially prevented the reduction in sodium excretion and creatinine clearance and significantly increased fractional excretion of sodium in glycerol treated rats suggesting a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…At this point, the argument is hypothetical, but it is not unreasonable to propose that the increased NOS activity is a response to significant vasoconstrictor stimulation in the established ARF kidney. Endogenous vasoconstrictor agonist activity, including endothelin-1, thromboxane A2, and renin-angiotensin, has been shown to be increased in ischemic ARF models (29)(30)(31). These agonists, in addition to endothelin-3, have been shown to induce endothelial NOS activity (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the argument is hypothetical, but it is not unreasonable to propose that the increased NOS activity is a response to significant vasoconstrictor stimulation in the established ARF kidney. Endogenous vasoconstrictor agonist activity, including endothelin-1, thromboxane A2, and renin-angiotensin, has been shown to be increased in ischemic ARF models (29)(30)(31). These agonists, in addition to endothelin-3, have been shown to induce endothelial NOS activity (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were measured: (1) Urinary and serum creatinine concentrations were deter mined by a method utilizing Fuller's earth in order to eliminate chro mogens [10,11]. Creatinine clearance (Ccr) was calculated as usual.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies it has been found that infusion of PGs [13][14][15][16] or inhibition ofTXA2 synthesis [10][11][12] pro tected against the development of ARF. Because CsA enhanced TXB2 (TXA2) and diminished PGs, we ex pected the NT induced by this agent to be more serious than that induced by substances such as glycerol (GRL) [10,11], mercuric chloride (MC) [24] and gentamicin (GM) [12] which were found to enhance both TXA2 and PG production.…”
Section: Effect O F Csa In Normal Ratsmentioning
confidence: 99%
See 2 more Smart Citations